cAMP-response element modulator tau is a positive regulator of testis angiotensin converting enzyme transcription. - Zhou, Y (1996)
Testis angiotensin-converting enzyme (ACE) is a unique form of ACE, only produced by male germ cells, and results from a testis-specific promoter found within the ACE gene. We have investigated the role of cAMP-response element modulator (CREM)tau in testis ACE transcription. In gel shift experiments, testes nuclear proteins retard an oligonucleotide containing the cAMP-response element (CRE) found at position -55 in the testis ACE promoter. Anti-CREM antibody supershifts this complex. Competitive gel shift shows that recombinant CREM tau protein and testis nuclear proteins have a similar specificity of binding to the tests ACE CRE. Functional analysis using in vitro transcription and transfection studies also demonstrate that CREM tau protein is a transcriptional activator of the testis ACE promoter. Western blot analysis identifies CREM tau protein in the protein-DNA complex formed between nuclear proteins and the testis ACE CRE motif. This analysis also identified other CREM isoforms in the gel-shifted complex, which are thought to be CREM tau 1/2, CREM alpha/beta, and S-CREM. These data indicate that CREM tau isoforms play an important role as a positive regulator in the tissue-specific expression of testis ACE.